Analisis Pertandingan Sepak Bola (UWCL) UEFA Women’s Champions League Antara Juventus Versus Barcelona - Mohammad Rivaldi Ihza Irwansyah; Achmad Widodo (Indonesian Journal of Kinanthropology (IJOK), 2022)
Background: Beside being useful for improving team competence, match analysis is also used by coaches to see the strengths of potential opponents. Not only before the game, but also during the game.Methods: The type of research used is quantitative research with a descriptive approach through observation and video analysis to determine the increase and decrease in Passing, Dribbling, Shooting, Heading, Throw-In, Foul, Off Side, Intercep, Seize the Ball, Protect the Ball, Save Goal Keeper, Goals. The sample of this research is the (UWCL) UEFA Women’s Champions League football match between Juventus vs Barcelona.Results: The result showed that the average passing, dribbling, shooting, heading team Juventus vs Barcelona in the (UWCL) UEFA Women’s Champions League match: Juventus' passing team had a percentage of 27% while Barcelona's passing team was more than the Juventus team which had a percentage of 73%. . The Juventus dribbling team has a percentage of 26% while the Barcelona team is more than the Juventus team which has a percentage of 74%. Shooting team Juventus has a percentage of 33% while the Barcelona team is more than the Juventus team which has a percentage of 67%. Heading team Juventus has a percentage of 43% while the Barcelona team is more than the Juventus team which has a percentage of 58%.Conclusions: based on the summary of the research resault and the description of the discusion, it can be concluded in terms of passing, dribbling, shooting, and heading techniques. The Barcelona team is more effective and more dominant than the Juventus team.